Respons generasi muda terhadap aplikasi E-kerajaan dan E-dagang - Mohd Yusof Hj.Abdullah,; Mohd Safar Hasim,; Fuziah Kartini Hassan Basri,; Mohamed Azul Mohamad Salleh,; Ali Salman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
Malaysia is one of the first developing countries that is at the forefront of development in ICT facilities. The use of ICT is to improve the country’s competitiveness, the modernization of the service sector, and to add value to quality of services of both the government and the private sector. Wide usage of ICT is already accepted by the Malaysian society. This article discusses the response of the young generation towards online applications which has been made available by the government and the private sector. Data and information was obtained from a study under the sponsorship of IRPA 2000-2006 which aims at looking at the level of acceptance readiness of various electronic applications and perception of respondents towards the various applications. The research methodoly used was survey on young generation in the age range 21 to 40 years. Some 1118 people in the age category in 15 towns of Malaysia were randomly chosen and interviewed using a set of questionnaire. Young generations are important segment of the society in any new development or innovation which has been introduced. The results of the study show that the usage of various electronic cards for various transactions has been adopted by the young generation. However, they are less confidence regarding the security of online transaction. This is because the young generations are always exposed to latest technological development and issues pertaining to its usage. Since young generation is important target for ICT, thereby they are deserved to be given confidence in using online service more widely